States, Markets, and Economic Growth - Флигстин, Нил (Journal of Economic Sociology, 2010)
In this paper I analyze two main phenomena in American economy which are usually considered to be crucial for free market development: “shareholder value” conception of firm, and development of Silicon Valley as innovation source of computer industry. The goal is to show that these phenomena appeared not only due to the entrepreneurs’ activity but also due to the fact that they are embedded in social relations. In both cases the state played the key role in organizing special conditions to the entrepreneurs’ activity.